2010
DOI: 10.1088/0022-3727/43/13/135403
|View full text |Cite
|
Sign up to set email alerts
|

Optical and magnetic properties of CuO nanowires grown by thermal oxidation

Abstract: CuO nanostructures with different morphologies, such as single-crystal nanowires, nanoribbons and nanorods, have been grown by thermal oxidation of copper in the (380-900) ºC temperature range. Cathodoluminescence spectra of the nanostructures show a band peaked at 1.31 eV which is associated to near band gap transitions of CuO. Two additional bands centred at about 1.23 eV and 1.11 eV, suggested to be due to defects, are observed for nanostructures grown at high temperatures. The magnetic behaviour of nanowir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…This kind of assignment was applied by some groups. Vila et al [ 36 ] observed luminescence bands centered at 1.33, 1.23, and 1.11 eV in CuO nanomaterial and suggested that the emission with highest energy corresponds to near band edge transition in CuO while the two other emissions are most probably introduced by oxygen vacancies and oxygen on copper antisite defects [ 35 , 37 , 38 ].…”
Section: Fundamental Propertiesmentioning
confidence: 99%
“…This kind of assignment was applied by some groups. Vila et al [ 36 ] observed luminescence bands centered at 1.33, 1.23, and 1.11 eV in CuO nanomaterial and suggested that the emission with highest energy corresponds to near band edge transition in CuO while the two other emissions are most probably introduced by oxygen vacancies and oxygen on copper antisite defects [ 35 , 37 , 38 ].…”
Section: Fundamental Propertiesmentioning
confidence: 99%
“…In order to utilize CuO for electrochemical and photoelectrochemical applications, it needs to be prepared as nanostructured thin films. Thin films of cupric oxide have been prepared by a number of techniques including pulsed laser deposition [3], thermal oxidation [4], ultrasonics spray pyrolysis [5], chemical bath deposition [6], microwave [7], sol-gel [8], electro-deposition [9], hydrothermal [10], sputtering [11], solvothermal [12], and successive ionic layer adsorption and reaction method [13]. All these preparation techniques offer distinct advantages depending on the kind of application.…”
Section: Introductionmentioning
confidence: 99%
“…Cupric oxide, CuO, which is a p-type semiconductor [1] (indirect bandgap of 1.2 to 1.5 eV) has been widely exploited for devices applications, such as an active electrode material for Li-ion batteries, field emission [FE]emitters, heterogeneous catalysts, gas sensors, hetrostructure and solar cells [2][3][4][5][6][7]. Several methods have been developed to prepare CuO nanostructures, such as chemical vapor deposition (CVD) [8], laser vaporization [9], electrochemical techniques [10], hydrothermal treatment [11] inexpensive wet chemical method [12], thermal oxidation methods [13] and the Sol-Gel method [14].…”
Section: Introductionmentioning
confidence: 99%